2006
DOI: 10.17221/3655-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Microspore Culture for Doubled Haploid Production in the Breeding Project "Czech Winter Rape"

Abstract: Winter rape (Brassica napus L. var. napus) is the most widespread oil plant and the second most frequently cultivated crop after cereals in the Czech Republic. Brassica napus L. is an allotetraploid or amphidiploid species with n = 19 chromosomes, derived from 2 diploid species B. oleracea (n = 9) and B. rapa (n = 10). The microspore doubled haploid (DH) methodology is now employed in many B. napus breeding programmes around the world as an alternative/supplement to conventional methods of homozygous line prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
0
8
0
2
Order By: Relevance
“…In other Brassica spp. it was reported that 33°C for 10 min, then 30°C for 40 min, and finally returned to 25°C continuously was optimal for B. napus (Anandarajah et al 1991), or 32°C for 8 days and 25°C continuously (Tian et al 2004), 30°C for 14 days continuously (Smýkalová et al 2006), 32°C for 3 days and 25°C continuously (Takahira et al 2010) for the same species; 32.5°C for 1 day and 25°C continuously for B. oleracea var. costata DC (Dias and Correia 2002); 32°C for 3 days and 25°C continuously (Chanana et al 2005), 35°C for 2 days then at 25°C continuously (Agarwal et al 2006;Ali et al 2008), or 4 ± 1°C for 10 days followed by 25°C continuously (Prem et al 2008) for B. juncea.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In other Brassica spp. it was reported that 33°C for 10 min, then 30°C for 40 min, and finally returned to 25°C continuously was optimal for B. napus (Anandarajah et al 1991), or 32°C for 8 days and 25°C continuously (Tian et al 2004), 30°C for 14 days continuously (Smýkalová et al 2006), 32°C for 3 days and 25°C continuously (Takahira et al 2010) for the same species; 32.5°C for 1 day and 25°C continuously for B. oleracea var. costata DC (Dias and Correia 2002); 32°C for 3 days and 25°C continuously (Chanana et al 2005), 35°C for 2 days then at 25°C continuously (Agarwal et al 2006;Ali et al 2008), or 4 ± 1°C for 10 days followed by 25°C continuously (Prem et al 2008) for B. juncea.…”
Section: Discussionmentioning
confidence: 98%
“…bud length) and developmental stage of immature pollen grains: most microspores at the late-uninucleate to early binucleate stage can undergo embryogenesis (Pechan and Keller 1988;Hansen and Svinnset 1993;Custers 2003;Prem et al 2005;Abraha et al 2008). The high response of microspore Zaki and Dickinson (1995) B. campestris Canadian Cv-2 5390 embryos/100 buds nr nr Guo and Pulli (1996) B. juncea Couve Algarvia 9 embryos/2 buds nr nr Dias and Correia (2002) B. juncea Rajat 3500 embryos/100 buds 52 nr Chanana et al (2005) Interspecific hybrid of B. napus L 365 embryos/3 buds nr nr Smýkalová et al (2006) HSH nr not reported, a under optimal conditions embryogenesis in the same developmental stage was also recorded in B. campestris (Guo and Pulli 1996), B. carinata (Abraha et al 2008), B. juncea (Chanana et al 2005;Agarwal et al 2006;Ali et al 2008;Prem et al 2008), B. napus cv. 'Topas' (Anandarajah et al 1991;Takahata and Keller 1991;Supena et al 2006), and B. oleracea var.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, in 1982, Lichter developed an isolated microspore culture system for B. napus. These techniques have been gradually developed and constantly improved (Cegielska-Taras et al, 2002;Forster and Thomas, 2005;Palmer et al, 2005;Smýkalová et al, 2006;Ferri and Keller, 2007;rev. Pratap et al, 2009;rev.…”
Section: Introductionmentioning
confidence: 99%
“…Базовый протокол технологии получения удвоенных гаплоидов с помощью культуры изолированных микроспор, разработанный в начале 1980-х годов (67) для рапса, адаптирован для представителей рода Brassica (68,69). Он успешно используется в разных странах, много сообщений по указанной тематике публикуют ученые из Индии (70), Канады (71), Чехии (72). В ФГБНУ ФНЦО разработан базовый протокол культуры микроспор in vitro для капустных культур 73 Исследования по получению удвоенных гаплоидов моркови в мире ведутся давно, но первые успехи достигнуты в последнее время.…”
unclassified